Analisis Kepuasan Pengguna Youtube Sebagai Media Belajar Mandiri Menggunakan Metode End User Computing Satisfaction (EUCS) - Oklatifa, Susi; Dodo Zaenal Abidin; Nurhadi (LPPM Universitas Dinamika Bangsa, 2025)
This study aims to analyze user satisfaction with YouTube as a self-learning platform among students at Universitas Dinamika Bangsa Jambi using the End User Computing Satisfaction (EUCS) method. The research examines five key EUCS dimensions: content, accuracy, format, ease of use, and timeliness. The research model was developed based on EUCS theory and tested using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS version 3.2.9. Data were collected through a survey questionnaire distributed to active students who utilize YouTube as a learning resource. A total of 387 respondents participated in this study, with all data deemed valid for analysis. The results indicate that accuracy, ease of use, and timeliness significantly influence user satisfaction, whereas content and format do not have a significant impact. These findings suggest that while YouTube offers accessibility and timely content, the quality of content and presentation format remain challenges to overall user satisfaction. This study highlights the importance of improving content curation and optimizing the user interface structure to enhance the learning experience on YouTube.